Human Disseminated Protothecosis: The Skin is the “Window”? - Wang, Xue; Ran, Yuanshuai; Jia, Songgan; Ahmed, Sarah; Long, Xuemei; Jiang, Yinhui; Jiang, Yanping (Frontiers in Immunology, 2022)
Human disseminated protothecosis is a rare infection caused by members of the genus Prototheca, an achlorophyllic algae always associated with debilitated hosts. The presence of non-budding cells and large, spherical cells (sporangia) with endosporulation (morula) in histology is proof of Prototheca infection. Regrettably, due to the lack of specificity of clinical features and low awareness among clinicians, protothecosis is always underestimated and misdiagnosed. The available data on a species-specific analysis of this infection are limited. In this review, we summarize the etiological, epidemiological, and clinical aspects of disseminated protothecosis. The potential pathogenicity and clinical differences between P. zopfii and P. wickerhamii were observed. Additionally, the skin not only became the main invasion site but also the most involved organ by the pathogen. With the increasing numbers of immunocompromised individuals throughout the world, the incidence of disseminated infection caused by Prototheca is bound to increase, and disseminated protothecosis that accompanies skin symptoms should be taken into account by clinicians.